Adherence of Female Health Care Workers to the Use a Web-Based Tool for Improving and Modifying Lifestyle: Prospective Target Group Pilot Study - Jukic, Tomislav; Ihan, Alojz; Petek Šter, Marija; Strojnik, Vojko; Stubljar, David; Starc, Andrej (JMIR Publications, 2020)
BackgroundHealth care professionals are exposed to the psychological and physiological effects of stress, which is a well-known risk factor for various mental and physical health problems. ObjectiveThe aims of this study were to assess the adherence of female health care workers to use a web-based tool for improving and modifying lifestyle and to identify the potential factors influencing their adherence. MethodsA prospective, observational study was performed. A total of 80 female health care workers (physicians and gradated nurses) from 2 university medical centers and female members of a family medicine society participated. Participants completed a questionnaire that inquired about their basic demographic data and physical fitness. Physical fitness was assessed by the Rockport Fitness Walking Test. Adherence to a web-based application (24@life) was followed for 3 months and the number of log-ins into the application was counted. ResultsThe study was conducted from March to October 2019. Significantly high workload has been detected in all groups (P<.05), except in the general practitioner with normal workload group. The graduated nurse working in the surgery room group showed chronic stress with elevated S-cortisol levels (>690 nmol/L); activated cellular immune system with elevated concentrations of lymphocytes (reference 1.1-2.5 × 109 cells/L), CD3 cells (reference 0.7-1.9 × 109 cells/L), CD8 cells (reference 0.2-0.7 × 109 cells/L), and HLA-DR/CD3 cells (reference 0.04-0.2 × 109 cells/L); and the worst quality of sleep (mean 2.8 [SD 1.2]). Only 32 of 80 participants (40%) were adherent to the web-based application. Participants most frequently viewed web pages on areas of physical activity (497 times) and nutrition (332 times). No factors or participant's characteristics such as weight (odds ratio [OR] 1.026, 95% CI 0.977-1.078), BMI (OR 0.993, 95% CI 0.834-1.184), age (OR 0.970, 95% CI 0.910-1.034), or stress level (OR 0.997, 95% CI 0.995-1.000) were identified to affect the adherence rates. ConclusionsFemale health care workers exposed to high workload did not find the web-based application useful for improving and modifying their lifestyle. Therefore, other strategies that might help health care workers facing stress and improve their lifestyle should be identified.